2021
DOI: 10.4103/joc.joc_55_21
|View full text |Cite
|
Sign up to set email alerts
|

Role of Endobronchial ultrasound guided transbronchial needle aspiration with cellblocks in diagnosis and subtyping of intrathoracic lesions: Two year experience from a tertiary care center

Abstract: Background: Endobronchial ultrasound guided transbronchial needle aspiration (EBUS-TBNA) allows precise real-time sampling of intrathoracic lesions and is a minimally invasive, safe, and cost effective technique with high diagnostic yield. The aim of the current study is to evaluate utility of EBUS-TBNA cytology with cellblocks (CBs) in the diagnosis and subtyping of the intrathoracic lesions. Materials and Methods: It was a prospective study conducted from October 2015… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The frequency of malignant EBUS-TBNA samples was 18.4-33.9% in the total population (ages 27-91 years old with a mean age of 61 years; ages 17-94 years old with a median age of 65.5 years) [1,11]. It was reported that 27.8-64.4% of patients had neoplastic diagnosis in patients who underwent EBUS-TBNA for intrathoracic lesions (ages 14-85 years old with a mean age of 48.4 years; ages 11-89 years old with a mean age of 63.5 years) [12,13]. In addition, the frequent disease types were different from those in older adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency of malignant EBUS-TBNA samples was 18.4-33.9% in the total population (ages 27-91 years old with a mean age of 61 years; ages 17-94 years old with a median age of 65.5 years) [1,11]. It was reported that 27.8-64.4% of patients had neoplastic diagnosis in patients who underwent EBUS-TBNA for intrathoracic lesions (ages 14-85 years old with a mean age of 48.4 years; ages 11-89 years old with a mean age of 63.5 years) [12,13]. In addition, the frequent disease types were different from those in older adults.…”
Section: Discussionmentioning
confidence: 99%
“…The most common location was a lymph node (83.3%). The mean number of needle passes from each site was 3.6 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). ROSE was performed in 91.8% of cases (236 cases) and correlated well with the final cytologic interpretation in 97.9%.…”
Section: Cytologic Findingsmentioning
confidence: 99%